Hydrogeochemistry of rock-water interaction and water quality around Bukit Mantri, balung, Tawau, Sabah - Mohd Shafreen Mad Isa (2023)
A study was carried out to characterise the geology, geochemistry, and mineralogy of hydrothermally altered andesite host to a gold mineralization system in Bukit Mantri area, Balung, Tawau. The main objective is to determine the hydrogeochemical composition, the status of water quality in waters draining the area; and to evaluate the potential of environmental degradation of mining. Geology of the study area is mainly delineated by the andesite country rocks. The andesite has been hydrothermally altered, and among the alteration profiles are argillic, propylic, silisic, and sulfuric. Geochemical analysis shows that SiO2 concentration is relatively higher in silicified andesite, K2O in propylitized andesite, and SO3 in sulfidized andesite. Moreover, the hydrothermal alterations also increased the concentration of trace elements in the andesite, such as As, Cu, Pb and Zn. As, Pb and Zn also found enriched in the volcanic breccia. Analyses on mineralogy show that quartz is the predominant mineral, followed by pyrite, and the hydrothermal fluids have introduced and enriched chlorite and K-feldspar in propylitized andesite, while acid leaching has caused the formation of clay minerals such as kaolinite and introduced muscovite in the argilized andesite. Pyrite found in the altered andesite strongly correlates with the concentration of SO3, implying higher acidity generation potential. On the other hand, analyses of the waters suggest that the water quality in the area is fresh, circumneutral, and has low redox potential, electrical conductivity, and dissolved solids. In the waters, the major cations and anions according to their dominancy order are Ca2+>Mg2+>K+>Na+, and SO42->HCO3->Cl-, respectively, whereas Na+>K+ and HCO3->SO42- are observed when under the influence of precipitation. Waters are classified into Ca-SO4 and mix types in mineralised sources drainages of Bukit Mantri andesite, and in Sungai Mantri, respectively. However, both are in CaMg-HCO3 type owing to weathering and excess of silicate minerals. The hydrogeochemistry of these waters is mainly attributed to the weathering of sulphides such as sulphide minerals, which intensifies closer to the mineralized area. The weathering of silicate minerals provides a sufficient buffer in these waters and retains them within circumneutral pH. The solubility of constituents is relatively low, in the descending order of Fe > Al > Mn > Zn > Ag > Ba > Pb > Cr > Cu > Co > Ni > Cd > As. Substantial changes in the solubility of these metals have been observed for Fe, Al, Mn, and Zn, associated with the relatively higher concentration in country rocks in the Bukit Mantri area and under the influence of mine development activities. The geoenvironmental model highlights the rock-water interaction and the result shows a possible deterioration of the water body due to increased acidity and higher metal constituents following mining activity if no mitigation measures are in place.